Physical and hydrological characteristics and modelling of the soil water retention curve in the brazilian semi-arid region (Bioscience Journal, 2022)
Semiarid regions are characterised by water scarcity, a limiting factor on plant growth and development. The Sertão Canal was built in the semiarid region of Brazil, more specifically in the state of Alagoas, with the aim of making year-round irrigation possible. However, for the best water management, a physical and hydrological knowledge of the soils is necessary. As such, the aim of this study was to determine the physical and hydrological characteristics of three different types of soil (Argisol, Quartzarenic Neossol and Regolithic Neossol) under native vegetation (Caatinga) and agricultural systems in the semiarid region of Alagoas, as well as to adjust the soil water retention characteristic curves. Soil samples were collected at depths of 0-10, 10-20 and 20-30 cm in the municipalities of Inhapi, Delmiro Gouveia and Pariconha, in the state of Alagoas. The points of the moisture characteristic curve were determined by the Richards method, at pressures of 33, 100, 500, 1000 and 1500 kPa. Retention curves were modelled using the exponential decay equation and compared using the van Genuchten equation, modelled with the help of the RETC computer software. Particle size varied according to the textural classification of the different soils, from Sand to a Sandy Clay Loam. The retention curve fluctuated due to the particle size of the soil, with the Red-Yellow Argisol (Inhapi) having a greater capacity for water retention. Extremely sandy soils, such as those in the Delmiro Gouveia region, had a low capacity for retaining water. For each soil sample, the exponential decay equation gave the best fit, with values for R2adjust of greater than 0.93. When the measured soil moisture levels were compared with the levels estimated by the RETC model, some of the treatments were unable to estimate accurately the moisture levels obtained with the soil water retention curves.